# SELINA Solutions for Class 10 Maths Chapter 8 - Remainder And Factor Theorems

Reach your exam performance goals with Selina Solutions for ICSE Class 10 Mathematics Chapter 8 Remainder and Factor Theorems. Learn how to solve problems using the remainder theorem. Revise the right steps to factorise a given expression by practising with our Selina solutions.

Get the necessary self-study materials to score high marks in your Maths exam at TopperLearning. You can find resources like ICSE Class 10 Maths sample question paper solutions, online practice tests etc. to study flexibly. If you need help grasping the concept of the remainder theorem, you can find support from experts by posting your queries through our ‘UnDoubt’ platform.

## Chapter 8 - Remainder And Factor Theorems Exercise Ex. 8(A)

Find, in each case, the remainder when:

By remainder theorem we know that when a polynomial f (x) is divided by x - a, then the remainder is f(a).

Show that:

(x - a) is a factor of a polynomial f(x) if the remainder, when f(x) is divided by (x - a), is 0, i.e., if f(a) = 0.

Use the Remainder Theorem to find which of the following is a factor of 2x^{3} + 3x^{2} - 5x - 6.

(i) x + 1

(ii) 2x - 1

(iii) x + 2

By remainder theorem we know that when a polynomial f (x) is divided by x - a, then the remainder is f(a).

Let f(x) = 2x^{3} + 3x^{2} - 5x - 6

(i) f (-1) = 2(-1)^{3} + 3(-1)^{2} - 5(-1) - 6 = -2 + 3 + 5 - 6 = 0

Thus, (x + 1) is a factor of the polynomial f(x).

(ii)

Thus, (2x - 1) is not a factor of the polynomial f(x).

(iii) f (-2) = 2(-2)^{3} + 3(-2)^{2} - 5(-2) - 6 = -16 + 12 + 10 - 6 = 0

Thus, (x + 2) is a factor of the polynomial f(x).

(i) If 2x + 1 is a factor of 2x^{2}
+ ax - 3, find the value of a.

(ii) Find the value of k, if 3x -
4 is a factor of expression 3x^{2} + 2x - k.

(i) 2x + 1 is a factor of f(x) =
2x^{2} + ax - 3.

(ii) 3x - 4 is a factor of g(x) =
3x^{2} + 2x - k.

Find the values of constants a and
b when x - 2 and x + 3 both are the factors of expression x^{3} + ax^{2}
+ bx - 12.

Let f(x) = x^{3} + ax^{2}
+ bx - 12

x - 2 = 0 x = 2

x - 2 is a factor of f(x). So, remainder = 0

x + 3 = 0 x = -3

x + 3 is a factor of f(x). So, remainder = 0

Adding (1) and (2), we get,

5a - 15 = 0

a = 3

Putting the value of a in (1), we get,

6 + b - 2 = 0

b = -4

find the value of k, if 2x + 1 is a factor of (3k + 2)x^{3} + (k - 1).

Let f(x) = (3k + 2)x^{3} + (k - 1)

2x + 1 = 0

Since, 2x + 1 is a factor of f(x), remainder is 0.

Find the value of a, if x - 2 is a
factor of 2x^{5} - 6x^{4} - 2ax^{3} + 6ax^{2}
+ 4ax + 8.

f(x) = 2x^{5} - 6x^{4}
- 2ax^{3} + 6ax^{2} + 4ax + 8

x - 2 = 0 x = 2

Since, x - 2 is a factor of f(x), remainder = 0.

2(2)^{5} - 6(2)^{4}
- 2a(2)^{3} + 6a(2)^{2} + 4a(2) + 8 = 0

64 - 96 - 16a + 24a + 8a + 8 = 0

-24 + 16a = 0

16a = 24

a = 1.5

Find the values of m and n so that
x - 1 and x + 2 both are factors of x^{3} + (3m + 1) x^{2} +
nx - 18.

Let f(x) = x^{3} + (3m +
1) x^{2} + nx - 18

x - 1 = 0 x = 1

x - 1 is a factor of f(x). So, remainder = 0

x + 2 = 0 x = -2

x + 2 is a factor of f(x). So, remainder = 0

Adding (1) and (2), we get,

9m - 27 = 0

m = 3

Putting the value of m in (1), we get,

3(3) + n - 16 =0

9 + n - 16 = 0

n = 7

When x^{3} + 2x^{2}
- kx + 4 is divided by x - 2, the remainder is k. Find the value of constant
k.

Let f(x) = x^{3} + 2x^{2}
- kx + 4

x - 2 = 0 x = 2

On dividing f(x) by x - 2, it leaves a remainder k.

Find the value of a, if the
division of ax^{3} + 9x^{2} + 4x - 10 by x + 3 leaves a
remainder 5.

Let f(x) = ax^{3} + 9x^{2}
+ 4x - 10

x + 3 = 0 x = -3

On dividing f(x) by x + 3, it leaves a remainder 5.

If x^{3} + ax^{2}
+ bx + 6 has x - 2 as a factor and leaves a remainder 3 when divided by x -
3, find the values of a and b.

Let f(x) = x^{3} + ax^{2}
+ bx + 6

x - 2 = 0 x = 2

Since, x - 2 is a factor, remainder = 0

x - 3 = 0 x = 3

On dividing f(x) by x - 3, it leaves a remainder 3.

Subtracting (i) from (ii), we get,

a + 3 = 0

a = -3

Substituting the value of a in (i), we get,

-6 + b + 7 = 0

b = -1

The expression 2x^{3} + ax^{2}
+ bx - 2 leaves remainder 7 and 0 when divided by 2x - 3 and x + 2
respectively. Calculate the values of a and b.

Let f(x) = 2x^{3} + ax^{2}
+ bx - 2

2x - 3 = 0 x =

On dividing f(x) by 2x - 3, it leaves a remainder 7.

x + 2 = 0 x = -2

On dividing f(x) by x + 2, it leaves a remainder 0.

Adding (i) and (ii), we get,

7a - 21 = 0

a = 3

Substituting the value of a in (i), we get,

9 + 2b - 3 = 0

2b = -6

b = -3

What number should be added to 3x^{3}
- 5x^{2} + 6x so that when resulting polynomial is divided by x - 3,
the remainder is 8?

Let the number k be added and the resulting polynomial be f(x).

So, f(x) = 3x^{3} - 5x^{2}
+ 6x + k

It is given that when f(x) is divided by (x - 3), the remainder is 8.

Thus, the required number is -46.

What number should be subtracted
from x^{3} + 3x^{2} - 8x + 14 so that on dividing it with x -
2, the remainder is 10.

Let the number to be subtracted be k and the resulting polynomial be f(x).

So, f(x) = x^{3} + 3x^{2}
- 8x + 14 - k

It is given that when f(x) is divided by (x - 2), the remainder is 10.

Thus, the required number is 8.

The polynomials 2x^{3} - 7x^{2} + ax - 6 and x^{3} - 8x^{2} + (2a + 1)x - 16 leaves the same remainder when divided by x - 2. Find the value of 'a'.

Let f(x) = 2x^{3} - 7x^{2} + ax - 6

x - 2 = 0 x = 2

When f(x) is divided by (x - 2), remainder = f(2)

Let g(x) = x^{3} - 8x^{2} + (2a + 1)x - 16

When g(x) is divided by (x - 2), remainder = g(2)

By the given condition, we have:

f(2) = g(2)

2a - 18 = 4a - 38

4a - 2a = 38 - 18

2a = 20

a = 10

Thus, the value of a is 10.

If (x - 2) is a factor of the expression 2x^{3} + ax^{2} + bx - 14 and when the expression is divided by (x - 3), it leaves a remainder 52, find the values of a and b

Find 'a' if the two polynomials ax^{3} + 3x^{2} - 9 and 2x^{3} + 4x + a, leave the same remainder when divided by x + 3.

## Chapter 8 - Remainder And Factor Theorems Exercise Ex. 8(B)

Using the Factor Theorem, show that:

(i) (x - 2) is a factor of x^{3} - 2x^{2} - 9x + 18. Hence, factorise the expression x^{3} - 2x^{2} - 9x + 18 completely.

(ii) (x + 5) is a factor of 2x^{3} + 5x^{2} - 28x - 15. Hence, factorise the expression 2x^{3} + 5x^{2} - 28x - 15 completely.

(iii) (3x + 2) is a factor of 3x^{3} + 2x^{2} - 3x - 2. Hence, factorise the expression 3x^{3} + 2x^{2} - 3x - 2 completely.

(i) Let f(x) = x^{3} - 2x^{2} - 9x + 18

x - 2 = 0 x = 2

Remainder = f(2)

= (2)^{3} - 2(2)^{2} - 9(2) + 18

= 8 - 8 - 18 + 18

= 0

Hence, (x - 2) is a factor of f(x).

Now, we have:

x^{3} - 2x^{2} - 9x + 18 = (x - 2) (x^{2} - 9) = (x - 2) (x + 3) (x - 3)

(ii) Let f(x) = 2x^{3} + 5x^{2} - 28x - 15

x + 5 = 0 x = -5

Remainder = f(-5)

= 2(-5)^{3} + 5(-5)^{2} - 28(-5) - 15

= -250 + 125 + 140 - 15

= -265 + 265

= 0

Hence, (x + 5) is a factor of f(x).

Now, we have:

2x^{3} + 5x^{2} - 28x - 15 = (x + 5) (2x^{2} - 5x - 3)

= (x + 5) [2x^{2} - 6x + x - 3]

= (x + 5) [2x(x - 3) + 1(x - 3)]

= (x + 5) (2x + 1) (x - 3)

(iii) Let f(x) = 3x^{3} + 2x^{2} - 3x - 2

3x + 2 = 0

Hence, (3x + 2) is a factor of f(x).

Now, we have:

Using the Remainder Theorem, factorise each of the following completely.

(i) 3x^{3 }+ 2x^{2} − 19x + 6

(ii) 2x^{3} + x^{2} - 13x + 6

(iii) 3x^{3} + 2x^{2} - 23x - 30

(iv) 4x^{3} + 7x^{2} - 36x - 63

(v) x^{3} + x^{2} - 4x - 4

(i)

(ii) Let f(x) = 2x^{3} + x^{2} - 13x + 6

For x = 2,

f(x) = f(2) = 2(2)^{3} + (2)^{2} - 13(2) + 6 = 16 + 4 - 26 + 6 = 0

Hence, (x - 2) is a factor of f(x).

(iii) f(x) = 3x^{3} + 2x^{2} - 23x - 30

For x = -2,

f(x) = f(-2) = 3(-2)^{3} + 2(-2)^{2} - 23(-2) - 30

= -24 + 8 + 46 - 30 = -54 + 54 = 0

Hence, (x + 2) is a factor of f(x).

(iv) f(x) = 4x^{3} + 7x^{2} - 36x - 63

For x = 3,

f(x) = f(3) = 4(3)^{3} + 7(3)^{2} - 36(3) - 63

= 108 + 63 - 108 - 63 = 0

Hence, (x + 3) is a factor of f(x).

(v) f(x) = x^{3} + x^{2} - 4x - 4

For x = -1,

f(x) = f(-1) = (-1)^{3} + (-1)^{2} - 4(-1) - 4

= -1 + 1 + 4 - 4 = 0

Hence, (x + 1) is a factor of f(x).

Using
the Remainder Theorem, factorise the expression 3x^{3} + 10x^{2}
+ x - 6. Hence, solve the equation 3x^{3} + 10x^{2} + x - 6 =
0.

Let
f(x) = 3x^{3} + 10x^{2} + x - 6

For x = -1,

f(x)
= f(-1) = 3(-1)^{3} + 10(-1)^{2} + (-1) - 6 = -3 + 10 - 1 - 6
= 0

Hence, (x + 1) is a factor of f(x).

Now,
3x^{3} + 10x^{2} + x - 6 = 0

Factorise
the expression f (x) = 2x^{3} - 7x^{2} - 3x + 18. Hence, find
all possible values of x for which f(x) = 0.

f
(x) = 2x^{3} - 7x^{2} - 3x + 18

For x = 2,

f(x)
= f(2) = 2(2)^{3} - 7(2)^{2} - 3(2) + 18

= 16 - 28 - 6 + 18 = 0

Hence, (x - 2) is a factor of f(x).

Given that x - 2 and x + 1 are factors of f(x) = x^{3} + 3x^{2} + ax + b; calculate the values of a and b. Hence, find all the factors of f(x).

f(x) = x^{3} + 3x^{2} + ax + b

Since, (x - 2) is a factor of f(x), f(2) = 0

(2)^{3} + 3(2)^{2} + a(2) + b = 0

8 + 12 + 2a + b = 0

2a + b + 20 = 0 ...(i)

Since, (x + 1) is a factor of f(x), f(-1) = 0

(-1)^{3} + 3(-1)^{2} + a(-1) + b = 0

-1 + 3 - a + b = 0

-a + b + 2 = 0 ...(ii)

Subtracting (ii) from (i), we get,

3a + 18 = 0

a = -6

Substituting the value of a in (ii), we get,

b = a - 2 = -6 - 2 = -8

f(x) = x^{3} + 3x^{2} - 6x - 8

Now, for x = -1,

f(x) = f(-1) = (-1)^{3} + 3(-1)^{2} - 6(-1) - 8 = -1 + 3 + 6 - 8 = 0

Hence, (x + 1) is a factor of f(x).

The expression 4x^{3} - bx^{2} + x - c leaves remainders 0 and 30 when divided by x + 1 and 2x - 3 respectively. Calculate the values of b and c. Hence, factorise the expression completely.

Let f(x) = 4x^{3} - bx^{2} + x - c

It is given that when f(x) is divided by (x + 1), the remainder is 0.

f(-1) = 0

4(-1)^{3} - b(-1)^{2} + (-1) - c = 0

-4 - b - 1 - c = 0

b + c + 5 = 0 ...(i)

It is given that when f(x) is divided by (2x - 3), the remainder is 30.

Multiplying (i) by 4 and subtracting it from (ii), we get,

5b + 40 = 0

b = -8

Substituting the value of b in (i), we get,

c = -5 + 8 = 3

Therefore, f(x) = 4x^{3} + 8x^{2} + x - 3

Now, for x = -1, we get,

f(x) = f(-1) = 4(-1)^{3} + 8(-1)^{2} + (-1) - 3 = -4 + 8 - 1 - 3 = 0

Hence, (x + 1) is a factor of f(x).

If
x + a is a common factor of expressions f(x) = x^{2} + px + q and
g(x) = x^{2} + mx + n; show that:

f(x)
= x^{2} + px + q

It is given that (x + a) is a factor of f(x).

g(x)
= x^{2} + mx + n

It is given that (x + a) is a factor of g(x).

From (i) and (ii), we get,

pa - q = ma - n

n - q = a(m - p)

Hence, proved.

The
polynomials ax^{3} + 3x^{2} - 3 and 2x^{3} - 5x + a,
when divided by x - 4, leave the same remainder in each case. Find the value
of a.

Let
f(x) = ax^{3} + 3x^{2} - 3

When f(x) is divided by (x - 4), remainder = f(4)

f(4)
= a(4)^{3} + 3(4)^{2} - 3 = 64a + 45

Let
g(x) = 2x^{3} - 5x + a

When g(x) is divided by (x - 4), remainder = g(4)

g(4)
= 2(4)^{3} - 5(4) + a = a + 108

It is given that f(4) = g(4)

64a + 45 = a + 108

63a = 63

a = 1

Find
the value of 'a', if (x - a) is a factor of x^{3} - ax^{2} +
x + 2.

Let
f(x) = x^{3} - ax^{2} + x + 2

It is given that (x - a) is a factor of f(x).

Remainder = f(a) = 0

a^{3}
- a^{3} + a + 2 = 0

a + 2 = 0

a = -2

Find
the number that must be subtracted from the polynomial 3y^{3} + y^{2}
- 22y + 15, so that the resulting polynomial is completely divisible by y +
3.

Let the number to be subtracted from the given polynomial be k.

Let
f(y) = 3y^{3} + y^{2} - 22y + 15 - k

It is given that f(y) is divisible by (y + 3).

Remainder = f(-3) = 0

3(-3)^{3}
+ (-3)^{2} - 22(-3) + 15 - k = 0

-81 + 9 + 66 + 15 - k = 0

9 - k = 0

k = 9

## Chapter 8 - Remainder And Factor Theorems Exercise Ex. 8(C)

Show
that (x - 1) is a factor of x^{3} - 7x^{2} + 14x - 8. Hence,
completely factorise the given expression.

Let
f(x) = x^{3} - 7x^{2} + 14x - 8

f(1)
= (1)^{3} - 7(1)^{2} + 14(1) - 8 = 1 - 7 + 14 - 8 = 0

Hence, (x - 1) is a factor of f(x).

Using Remainder Theorem, factorise:

x^{3} + 10x^{2} - 37x + 26 completely.

When
x^{3} + 3x^{2} - mx + 4 is divided by x - 2, the remainder is
m + 3. Find the value of m.

Let
f(x) = x^{3} + 3x^{2} - mx + 4

According to the given information,

f(2) = m + 3

(2)^{3}
+ 3(2)^{2} - m(2) + 4 = m + 3

8 + 12 - 2m + 4 = m + 3

24 - 3 = m + 2m

3m = 21

m = 7

What
should be subtracted from 3x^{3} - 8x^{2} + 4x - 3, so that
the resulting expression has x + 2 as a factor?

Let the required number be k.

Let
f(x) = 3x^{3} - 8x^{2} + 4x - 3 - k

According to the given information,

f (-2) = 0

3(-2)^{3}
- 8(-2)^{2} + 4(-2) - 3 - k = 0

-24 - 32 - 8 - 3 - k = 0

-67 - k = 0

k = -67

Thus, the required number is -67.

If (x + 1) and (x - 2) are factors of x^{3} + (a + 1)x^{2} - (b - 2)x - 6, find the values of a and b. And then, factorise the given expression completely.

Let f(x) = x^{3} + (a + 1)x^{2} - (b - 2)x - 6

Since, (x + 1) is a factor of f(x).

Remainder = f(-1) = 0

(-1)^{3} + (a + 1)(-1)^{2} - (b - 2) (-1) - 6 = 0

-1 + (a + 1) + (b - 2) - 6 = 0

a + b - 8 = 0 ...(i)

Since, (x - 2) is a factor of f(x).

Remainder = f(2) = 0

(2)^{3} + (a + 1) (2)^{2} - (b - 2) (2) - 6 = 0

8 + 4a + 4 - 2b + 4 - 6 = 0

4a - 2b + 10 = 0

2a - b + 5 = 0 ...(ii)

Adding (i) and (ii), we get,

3a - 3 = 0

a = 1

Substituting the value of a in (i), we get,

1 + b - 8 = 0

b = 7

f(x) = x^{3} + 2x^{2} - 5x - 6

Now, (x + 1) and (x - 2) are factors of f(x). Hence, (x + 1) (x - 2) = x^{2} - x - 2 is a factor of f(x).

f(x) = x^{3} + 2x^{2} - 5x - 6 = (x + 1) (x - 2) (x + 3)

If x - 2 is a factor of x^{2} + ax + b and a + b = 1, find the values of a and b.

Let f(x) = x^{2} + ax + b

Since, (x - 2) is a factor of f(x).

Remainder = f(2) = 0

(2)^{2} + a(2) + b = 0

4 + 2a + b = 0

2a + b = -4 ...(i)

It is given that:

a + b = 1 ...(ii)

Subtracting (ii) from (i), we get,

a = -5

Substituting the value of a in (ii), we get,

b = 1 - (-5) = 6

Factorise
x^{3} + 6x^{2} + 11x + 6 completely using factor theorem.

Let
f(x) = x^{3} + 6x^{2} + 11x + 6

For x = -1

f(-1)
= (-1)^{3} + 6(-1)^{2} + 11(-1) + 6

= -1 + 6 - 11 + 6 = 12 - 12 = 0

Hence, (x + 1) is a factor of f(x).

Find
the value of 'm', if mx^{3} + 2x^{2} - 3 and x^{2} -
mx + 4 leave the same remainder when each is divided by x - 2.

Let
f(x) = mx^{3} + 2x^{2} - 3

g(x)
= x^{2} - mx + 4

It is given that f(x) and g(x) leave the same remainder when divided by (x - 2). Therefore, we have:

f (2) = g (2)

m(2)^{3}
+ 2(2)^{2} - 3 = (2)^{2} - m(2) + 4

8m + 8 - 3 = 4 - 2m + 4

10m = 3

m =

The polynomial px^{3} + 4x^{2} - 3x + q is completely divisible by x^{2} - 1; find the values of p and q. Also, for these values of p and q factorize the given polynomial completely.

Let f(x) = px^{3} + 4x^{2} - 3x + q

It is given that f(x) is completely divisible by (x^{2} - 1) = (x + 1)(x - 1).

Therefore, f(1) = 0 and f(-1) = 0

f(1) = p(1)^{3} + 4(1)^{2} - 3(1) + q = 0

p + q + 1 = 0 ...(i)

f(-1) = p(-1)^{3} + 4(-1)^{2} - 3(-1) + q = 0

-p + q + 7 = 0 ...(ii)

Adding (i) and (ii), we get,

2q + 8 = 0

q = -4

Substituting the value of q in (i), we get,

p = -q - 1 = 4 - 1 = 3

f(x) = 3x^{3} + 4x^{2} - 3x - 4

Given that f(x) is completely divisible by (x^{2} - 1).

Find
the number which should be added to x^{2} + x + 3 so that the
resulting polynomial is completely divisible by (x + 3).

Let the required number be k.

Let
f(x) = x^{2} + x + 3 + k

It is given that f(x) is divisible by (x + 3).

Remainder = 0

f (-3) = 0

(-3)^{2}
+ (-3) + 3 + k = 0

9 - 3 + 3 + k = 0

9 + k = 0

k = -9

Thus, the required number is -9.

When the polynomial x^{3} + 2x^{2} - 5ax - 7 is divided by (x - 1), the remainder is A and when the polynomial x^{3} + ax^{2} - 12x + 16 is divided by (x + 2), the remainder is B. Find the value of 'a' if 2A + B = 0.

It is given that when the polynomial x^{3} + 2x^{2} - 5ax - 7 is divided by (x - 1), the remainder is A.

(1)^{3} + 2(1)^{2} - 5a(1) - 7 = A

1 + 2 - 5a - 7 = A

- 5a - 4 = A ...(i)

It is also given that when the polynomial x^{3} + ax^{2} - 12x + 16 is divided by (x + 2), the remainder is B.

x^{3} + ax^{2} - 12x + 16 = B

(-2)^{3} + a(-2)^{2} - 12(-2) + 16 = B

-8 + 4a + 24 + 16 = B

4a + 32 = B ...(ii)

It is also given that 2A + B = 0

Using (i) and (ii), we get,

2(-5a - 4) + 4a + 32 = 0

-10a - 8 + 4a + 32 = 0

-6a + 24 = 0

6a = 24

a = 4

(3x
+ 5) is a factor of the polynomial (a - 1)x^{3} + (a + 1)x^{2}
- (2a + 1)x - 15. Find the value of 'a', factorise the given polynomial
completely.

Let
f(x) = (a - 1)x^{3} + (a + 1)x^{2} - (2a + 1)x - 15

It is given that (3x + 5) is a factor of f(x).

f(x) = (a - 1)x^{3}
+ (a + 1)x^{2} - (2a + 1)x - 15

= 3x^{3} + 5x^{2} - 9x - 15

When
divided by x - 3 the polynomials x^{3} - px^{2} + x + 6 and
2x^{3} - x^{2} - (p + 3) x - 6 leave the same remainder. Find
the value of 'p'.

If
(x - 3) divides f(x) = x^{3} - px^{2} + x + 6, then,

Remainder
= f(3) = 3^{3} - p(3)^{2} + 3 + 6 = 36 - 9p

If
(x - 3) divides g(x) = 2x^{3} - x^{2} - (p + 3) x - 6, then

Remainder
= g(3) = 2(3)^{3} - (3)^{2} - (p + 3) (3) - 6 = 30 - 3p

Now, f(3) = g(3)

36 - 9p = 30 - 3p

-6p = -6

p = 1

Use the Remainder Theorem to factorise the following expression:

2x^{3}
+ x^{2} - 13x + 6

f(x) = 2x^{3} + x^{2} - 13x + 6

Factors of constant term 6 are 1, 2, 3, 6.

Putting x = 2, we have:

f(2) = 2(2)^{3} + 2^{2} - 13 (2) + 6
= 16 + 4 - 26 + 6 = 0

Hence (x - 2) is a factor of f(x).

Using remainder theorem, find the
value of k if on dividing 2x^{3} + 3x^{2} - kx + 5 by x - 2, leaves a remainder 7.

Let f(x) = 2x^{3} + 3x^{2} - kx
+ 5

Using Remainder Theorem, we have

f(2) = 7

∴ 2(2)^{3}
+ 3(2)^{2} - k(2) + 5 = 7

∴ 16 + 12 - 2k + 5 = 7

∴ 33 - 2k = 7

∴ 2k = 26

∴ k = 13

What must be subtracted from 16x^{3} - 8x^{2} + 4x + 7 so
that the resulting expression has 2x + 1 as a factor?

Here, f(x) = 16x^{3} - 8x^{2} + 4x + 7

Let the number subtracted be k from the given polynomial f(x).

Given that 2x + 1 is a factor of f(x).

Therefore 1 must be subtracted from 16x^{3} - 8x^{2} +
4x + 7 so that the resulting expression has 2x + 1 as a factor.

### Kindly Sign up for a personalised experience

- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions

#### Sign Up

#### Verify mobile number

Enter the OTP sent to your number

Change